Konsep Berinfak Dalam Alquran: Studi Penafsiran Makna Kata “Basith” Dalam Surah Al Isra’ Ayat 29 Dalam Perspektif Ibnu Kaṡir - Amy Rejha; Ahmad Zuhri; Yuzaidi Yuzaidi (Dakwatussifa: Journal of Da'wah and Communication, 2023)
Infaq is a middle way to overcome the nature of waste and stinginess that exist in humans. Allah commands His servants to spend some of the good fortune he has given as a form of gratitude and concern for others. So from there I took this title to clarify the meaning of the word "Basith". By looking for references from the book of interpretation by the interpretation of Ibn Kathir.This study uses library research (library research), in library research in collecting data through analyzing books of books that are related and have a relationship in supporting this research. And also the author looks at the conditions in the field regarding the concept of influencing social life. From the results of this study, the authors found that when examined, the word basith in various verse contexts does not only mean "expanding" as most people only understand with that meaning. The word Basith has a variety of different meanings such as "excessive" and some say "wasteful". Keywords: Basith, Exaggeration